Ring-Opening Products of 1-Phenyltricyclo[4.1.0.02,7]-heptane and 2-Phenyltricyclo[4.1.0.02,7]heptane in SiO2 - BUDAK, YAKUP; FINDIK, ESRA; BURCU GURDURE, M.; CEYLAN, MUSTAFA (Asian Journal of Chemistry, 2010)
Treatment of the mixture of 1-phenyltricyclo[4.1.0.02,7]- heptane (8) and 2-phenyltricyclo[4.1.0.02,7]heptane (15) with SiO2 gave the ring-opening products i.e., 2-phenylbicyclo- [4.1.0]hept-2-ene (19), 1-phenylbicyclo[4.1.0]hept-2-ene (20), (1E,4Z)-2-phenylcyclohepta-1,4-diene (21), (E)-3- phenylcyclohept-3-en-1-ol (22) and 1-phenylbicyclo[4.1.0]- heptan-2-ol (23). In addition to these products, phenyl (1-phenylbicyclo[4.1.0]heptan-2-yl)sulfane (18) and (Z)- phenyl(2-phenylcyclohept-3-enyl)sulfane (17) were obtained by the addition of PhSH to the mixture of 8 and 15. The addition of bromine to the mixture of 8 and 15 gave 2-bromomethylbiphenyl as the main product.